Examining Treatment Outcomes Across Contexts: How Do Child Baseline Characteristics Impact Measurement of Treatment Response? - Grzadzinski, Rebecca; Jatkar, Alapika; Donovan, Kevin; Truong, Kinh; Holbrook, Alison; Lord, Catherine; Kim, So Hyun (Journal of Autism & Developmental Disorders, 2023)
The evaluation of the overlap between the ADOS BOSCC and Standard BOSCC as well as the exploration of child characteristics that may predict change are important steps in consolidating data-driven definitions of "improvement". Participants were seen between 2 and 5 times with Standard BOSCC and ADOS BOSCC observations over the course of early intervention trials (Grzadzinski et al. in J Autism Dev Disord 46:2464, 2016; Kim et al. in Autism 23:5, 2019). Results showed consistency between the Standard BOSCC and ADOS BOSCC, highlighting the utility of both as metrics of change and treatment outcome across contexts. Baseline characteristics may play a role in the tailoring of early intervention to maximize treatment outcome and may offer guidance when determining which outcome measures to use.